Role of lifestyle factors on the development and long-term prognosis of pneumonia and cardiovascular disease in the Chinese population - Yizhen Hu; Qiufen Sun; Yuting Han; Canqing Yu; Yu Guo; Dianjianyi Sun; Yuanjie Pang; Pei Pei; Ling Yang; Yiping Chen; Huaidong Du; Mengwei Wang; et al. (Chinese Medical Journal)
Abstract. Background:. Whether adherence to a healthy lifestyle is associated with a lower risk of developing pneumonia and a better long-term prognosis remains unclear. This study aimed to investigate associations of individual and combined lifestyle factors (LFs) with the incidence risk and long-term prognosis of pneumonia hospitalization. Methods:. Using data from the China Kadoorie Biobank study, we used the multistate models to investigate the role of five high-risk LFs, including smoking, excessive alcohol drinking, unhealthy dietary habits, physical inactivity, and unhealthy body shape, alone or in combination in the transitions from a generally healthy state at baseline to pneumonia hospitalization or cardiovascular disease (CVD, regarded as a reference outcome), and subsequently to mortality. Results:. Most of the five high-risk LFs were associated with increased risks of transitions from baseline to pneumonia and from pneumonia to death, but with different risk estimates. The greater the number of high-risk LFs, the higher the risk of developing pneumonia and long-term mortality risk after pneumonia, with the strength of associations comparable to that of LFs and CVD. Compared to participants with 0–1 high-risk LF, the adjusted hazard ratios (HRs) and 95% confidence intervals (CIs) for transitions from baseline to pneumonia and from pneumonia to death in those with five high-risk LFs were 1.43 (1.28–1.60) and 1.98 (1.61–2.42), respectively. Correspondingly, the respective HRs (95% CIs) for transitions from baseline to CVD and from CVD to death were 2.00 (1.89–2.11) and 1.44 (1.30–1.59), respectively. The risk estimates changed slightly when further adjusting for the presence of major chronic diseases. Conclusion:. In this Chinese population, unhealthy LFs were associated with an increased incidence and long-term mortality risk of pneumonia.